Ageing and the Glomerular Filtration Rate: Truths and Consequences - Glassock, Richard J. (American Clinical and Climatological Association, 2009)
The process of glomerular filtration of plasma fluid has been known for over 160 years and the measurement of the rate of its formation (glomerular filtration rate, GFR) has been possible for over 80 years. Studies conducted in the 1930's to the 1950's clearly established that GFR declines, perhaps inexorably, with normal ageing, usually beginning after 30–40 years of age. The rate of decline may accelerate after age 50–60 years. This decline appears to be a part of the normal physiologic process of cellular and organ senescence and is associated with structural changes in the kidneys. In the last decade a new paradigm has been introduced in which the true or measured GFR is estimated (eGFR) by formulas based on serum creatinine levels and in which these estimates are applied to the diagnoses of chronic kidney disease (CKD) in the general population. These criteria for diagnosis of CKD include an absolute threshold for eGFR, unadjusted for the effects of age on the normal values for eGFR. A consequence of these criteria has been to overstate the frequency of CKD in the general population and to generate many “false positive” diagnoses of CKD. This paper discusses the known effects of ageing on GFR and the consequences of using a classification system for defining CKD that does not take into account the normal decline of GFR with ageing.